Comparative dynamic response of mesomachine tool structures. (5th May 2009) - Jackson, Mark J.; Hyde, Luke J.; Robinson, Grant M.; Ahmed, Waqar
The dynamic characteristics of a machine tool structure used for machining engineering components at the microscale requires minimising the effects of vibrations. This requires a machine tool to be rigid and to be able to dissipate heat and vibrating waves in a symmetrical fashion. The idea for the structure comes from the structural stability afforded by using a tetrahedral geometry. The tetrahedral structure is a stable structure and it is considered that the geometry could minimise vibrations than conventional machine tool designs. The reason lies in the way that the structure is kinematically balanced. To explore the hypothesis, an experimental modal analysis established the vibration characteristics of the structure and of a conventional machine tool. Modal analysis consisted of measuring the Frequency Response Functions (FRFs) from impact tests to determine the natural frequencies, damping and mode shapes of the machine tool structures. A finite-element model was compared with the experimental data, thus validating the model so that it may be used for modelling future changes to the design of mesomachine tools.